Quando morre um filho, morre também uma mãe: violência de Estado e descolonização - Aguiar, Claudia Cristina Trigo de (2021)
In this research, carried out with the Mães em Luto da Zona Leste (East Zone Mothers in Mourning) movement (São Paulo, capital), set up by mothers and family members whose sons were murdered by state agents, we considered the suffering of the mothers, who call themselves living dead, in a certain radicality and we bet that the public enunciation and circulation of their words and silences question the logic that engender the black youth genocide. In the methodological perspective of the cartographic intervention research, we followed mothers and family members in different contexts and listening and enunciation devices - talks and public hearings, their movements’ meetings, interviews and conversation circles with mothers and public policy actors and through a clinical-political writing group device that evolved into a book: Mães em Luta (Mothers in Struggle). The transcripts and diary notes resulting from this monitoring are presented in the form of narratives that condense an analyzing dimension of the mothers' experience. We present such narratives as opening texts or in the course of what we call ‘trail’. The five trails articulate the narratives with the analytical perspective of feminism, the studies by Mbembe and Fanon on colonization/decolonization, the clinical and political reading of suffering and the psychosocial impacts of State violence. We understand that these youths’ deaths regulate black women's access to maternity, updating the experience of enslavement, through death policies built by racism, making them targets of state violence. However, the violence that affects their bodies is prior to the one which affects their offspring. The struggle of these women reveals a way of managing the city in which state violence affects, simultaneously, bodies, access to / in motherhood and territories, producing contexts of youth massacre. To demand justice against their son's death, they travel through the justice system, where a criminal son and a broken family are imposed on them. Recurring denials to the mothers' demands for justice privatize the damage suffered, operating another massacre aimed at their ways of mothering. From a clinical-political perspective, we problematize trauma and melancholia as psychopathologies that dispute their presence in these contexts. The sons’ murder is intolerable, throwing the mothers into the condition of living death: when a son dies, a mother also dies, as they say. Furthermore, some make their bodies the presence of their children, raw flesh testimony, a fight against oblivion. Such suffering affects family members, territory and society for generations. Impunity produces an excruciating repetition of trauma. We have proposed the revolt as the trace of the intolerable, lived as a bodily insurgency. There is no return to a destroyed world, this is the radicality of traumatic suffering. In order to (re)live, it is the revolt that makes it possible to (re)invent their lives, a work of not dying completely. This possibility depends on the social recognition of this suffering, imposing the task of collapsing the logic that produce these bodies as criminals. Thus, we have to affirm the clinic as resistance, inseparable from the debate on political and social reparation in the face of crimes of enslavement and other state violence that sustain silence before the black youth genocide